Workshop digital marketing dan implementasi media sosial untuk akselerasi penjualan bagi pelaku UMKM di kelurahan Kedung Baruk Surabaya - Slamet Slamet; Siswo Martono (Universitas Pendidikan Indonesia (UPI), 2022)
MSMEs have been proven to be able to encourage the country's economic progress. The existence of MSMEs cannot be eliminated or avoided from the nation's society today. Its existence is very useful in terms of distribution of community income. The problem that is often experienced by MSME actors is the lack of experience in managing their business. Many of the MSME players only focus on producing goods, but do not think about how to expand their business. The effect is that it is difficult to increase the business and the business that is carried out is running in place. In addition, the difficulty in distributing goods is a factor that causes the distribution of goods to be less widespread. This is because the perpetrators have not been able to do their marketing online and after that the average of these MSMEs experienced a decline in sales and distribution of goods. From the problems faced, an appropriate business development strategy is needed and the important role of the government. The internet technology-based coaching approach is carried out for MSME actors. The development of the internet supports progress in all aspects including business and business transactions using digital marketing and social media that can be used by MSME actors in increasing sales and developing their business. This community service activity is carried out for MSME actors, in Kedung Baruk Village, Surabaya. It is recorded that 17 MSMEs are engaged in food and beverage, handicrafts, grocery stores, printing, and fashion.